2010
DOI: 10.1007/s00535-010-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection as a treatment for gastric noninvasive neoplasia: a multicenter study by Osaka University ESD Study Group

Abstract: In this large-scale, multicenter cross-sectional study, over 40% of the noninvasive gastric neoplasia specimens were determined to have adenocarcinoma, and the ESD-related complication rate was relatively low. Therefore, ESD was useful and may be a therapeutic option for gastric NIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 18 publications
2
77
0
2
Order By: Relevance
“…The depressed type is also reported to have more malignant potential. We, however, revealed that even patients with both smaller and elevated neoplasms had a greater than 40% under-diagnosis rate [27] . Similarly, cancer foci have been reported in hyperplastic polyps with a diameter of 5 mm [31] .…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The depressed type is also reported to have more malignant potential. We, however, revealed that even patients with both smaller and elevated neoplasms had a greater than 40% under-diagnosis rate [27] . Similarly, cancer foci have been reported in hyperplastic polyps with a diameter of 5 mm [31] .…”
mentioning
confidence: 62%
“…We recently reported that the underdiagnosis rate of intraepithelial neoplasia proven by biopsy was 44% (95% CI: 39%-49%). Moreover, in that study, there were 2 lesions (0.42%) of adenocarcinoma with submucosal invasion of more than 500 μm, one of which involved the lymphatic system [27] . The reasons for the difficulty in making an accurate diagnosis based on a biopsy specimen are as follows: (1)the structural atypia of both adenoma and well-differentiated adenocarcinoma is too subtle to detect in small biopsy specimens; (2) cancer sometimes exists focally in the lesion and a sampling error might occur; and (3) regeneration of atypia induced by gastritis induces histological modification (Figure 1).…”
Section: Difficulty Of Accurate Diagnosis Based On Biopsymentioning
confidence: 77%
“…Endoscopic submucosal dissection (ESD) for ESCNs is an endoluminal therapeutic technique to dissect directly along the submucosal layer. ESD was developed in Japan for the surgical treatment of gastric cancer and gave high curative resection rates for early gastric cancer, regardless of tumor size [18][19][20][21][22][23] . Hence, the technique has also been introduced for the esophagus [24] and was approved for the treatment of esophageal cancer by the Japanese government in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. László Czakó et al for their letter and interest regarding our article [1]. Dr. Czakó et al made the following points concerning the strategy for treating gastric non-invasive neoplasia (NIN): (1) gastric NIN should be endoscopically resected; (2) concerning the modality of the treatment, endoscopic mucosal resection (EMR) may be recommended for the removal of small (\5 mm), elevated lesions, and endoscopic submucosal dissection (ESD) would be preferred for larger or depressed lesions.…”
mentioning
confidence: 90%